Literacy Development Through Literature: A Comprehensive Review - Sutriani, Sutriani (Majapahit Journal of English Studies, 2025)
Literacy development is a cornerstone of educational success and lifelong learning. This article explores the role of literature in fostering literacy skills, drawing on a comprehensive review of existing research. The study examines how exposure to literature enhances reading comprehension, vocabulary acquisition, critical thinking, and cultural awareness. By analyzing various theoretical frameworks and empirical studies, this article highlights effective strategies for integrating literature into literacy instruction. The findings suggest that literature-based approaches not only improve academic outcomes but also cultivate a love for reading and deeper engagement with texts. The article concludes with recommendations for educators and policymakers to prioritize literature-rich environments in literacy education.